About the problems of teaching information and communication technologies in the conditions of information society - A., Turumbetova L.; A., Tyulepberdinova G.; N., Issabayeva S. (Farabi Journal of Social Sciences, 2019)
Abstract. This article focuses on the education problems in Kazakhstan. The processes of informatization of society in the second half of the XX century and its continuation in the XXI century, transformation of information and knowledge have led to the emergence of the information society, characterized by a high level of information intensity in the everyday life of most citizens; by the use of technology for a wide range of personal, social, educational and business activities, by rapid transition and exchange of digital data between places irrespective of distance. The information age and the networked world are forcing educators to rethink the educational experience. Modern society requires new approaches to training specialists on a global level. Graduates of the university should not only have good knowledge of their field, have competencies that are formed by professional skills, but speak in three languages: Kazakh, Russian and English at the professional level. Kazakhstan education system must be able not only to give knowledge, but also, due to the huge flow of new information, be aimed at continuous self-education, self-mastery of the information. The authors point out the importance of the subject «Information and communication technologies» which must be taught in English since 2016 as a compulsory subject in the curriculum of higher education institutions. In this regard, there is a sharp demand for specialists in the field of Computer science. The authors consider that these specialists must be professionally trilingual.